Design of a Self-Phased Quadrifilar Helix Antenna for Satellite Communication - Narimani, R.; Farhoudi, L. (Engineering, Technology & Applied Science Research, 2017)
The objective of this study is the design and implementation of a Quadrifilar Helix Antenna (QHA) for telemetry, tracking and control of a Low Earth Orbit (LEO) satellite. Because of its cardioid-shaped circularly polarized beam, QHA can satisfy requirements of satellite communications completely. In this paper, a variation of QHA referred to as “self-phased QHA” with a single feeding circuit, has been proposed to reduce implementation complexity. The designed antenna has been analyzed and the experimental results show that the radiation pattern provides good wide-beam in the desired frequency while the antenna’s bandwidth is around 200MHz when VSWR is less than 2.